Immediacy, or, The style of too-late capitalism / Anna Kornbluh. - Kornbluh, Anna (Verso, 2024)
Contemporary cultural style boosts transparency and instantaneity. These are values absorbed from our current economic conditions of 'disintermediation': cutting out the middleman. Like Uber, but for art. This resource names this style to make sense of what we lose when the contradictions of 21st-century capitalism demand that aesthetics negate mediation. Surging realness as an aesthetic program synchs with the economic imperative to intensify circulation when production stagnates. This book explains the recent obsession with immersion and today's intolerance of representation, and points to alternative forms in photography, TV, novels, and constructive theory that prioritise distance, impersonality, and big ideas instead.